2012
DOI: 10.1016/j.jenvman.2011.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen removal from landfill leachate in constructed wetlands with reed and willow: Redox potential in the root zone

Abstract: a b s t r a c tThis study investigated the effects of reed and willow on bioremediation of landfill leachate in comparison with an unplanted control by measuring redox potential levels in the rhizosphere of microcosm systems in a greenhouse. Plants had a significant influence on redox potential relative to the plant-less system. Redox potential in the reed rhizosphere was anoxic (mean À102 AE 85 mV), but it was the least negative, being significantly higher than in the willow (mean À286 AE 118 mV), which had t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 20 publications
0
31
0
1
Order By: Relevance
“…They also claimed that organic loading and ammonia were the factors that affected the biodegradation. In another work, Białowiec et al (2012) compared reed and willow with an unplanted control by measuring redox potential levels in the rhizosphere of microcosm system for the leachate bioremediation. The results suggested that redox potential in the reed rhizosphere was anoxic (mean -102 ± 85 mV), but it was the least negative, being significantly higher than in the willow (mean -286 ± 118 mV), which had the lowest Eh.…”
Section: Bioreactormentioning
confidence: 99%
“…They also claimed that organic loading and ammonia were the factors that affected the biodegradation. In another work, Białowiec et al (2012) compared reed and willow with an unplanted control by measuring redox potential levels in the rhizosphere of microcosm system for the leachate bioremediation. The results suggested that redox potential in the reed rhizosphere was anoxic (mean -102 ± 85 mV), but it was the least negative, being significantly higher than in the willow (mean -286 ± 118 mV), which had the lowest Eh.…”
Section: Bioreactormentioning
confidence: 99%
“…To meet discharge standards, the conventional methods that generate residues are saddled with high initial and operational costs and low applicability to a wide variety of pollutants, among others [14][15][16][17][18][19][20][21]. In recent years, an increasing number of research looks into the potential application of other adsorbents (e.g., agricultural waste or natural polymers and by-products of industrial processes) to achieve appropriate leachate treatment or as an alternative approach to conventional media for the treatment of pollutants that exist wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…Ultimately,75.39 and 84.90 % NO 3 − -N was removed, respectively. Previous studies reported that Salix could remove large amounts of N and P in constructed wetlands (Wu et al 2011;Białowiec et al 2012). In the present study, similar trends were observed.…”
Section: Nitrogen Removalmentioning
confidence: 99%
“…The application of economic plants for wastewater phytoremediation includes constructed wetlands (Białowiec et al 2012;Leto et al 2013;Türker et al 2013), a hydroponic nutrient film technique system (Vaillant et al 2002(Vaillant et al , 2003Hu et al 2008), and a floating mat economic plant-based treatment system (Sooknah and Wilkie 2004;Sun et al 2009;Li et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation